1999
DOI: 10.1006/dbio.1998.9129
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function ofGdf-5during Digit Skeletogenesis in the Embryonic Chick Leg Bud

Abstract: Bone morphogenetic proteins (BMPs) constitute a large family of secreted signals involved in the formation of the skeleton but the specific function of each member of this family remains elusive. GDF-5 is a member of the BMP family which has been implicated in several skeletogenic events including the induction and growth of the appendicular cartilages, the determination of joint forming regions, and the establishment of tendons. Here, we have studied the function of GDF-5 in digit skeletogenesis by analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(161 citation statements)
references
References 46 publications
8
149
2
Order By: Relevance
“…Bone morphogenetic protein (BMP) signaling is a major positive regulator of chondrogenesis (Duprez et al, 1996;Francis-West et al, 1996;Merino et al, 1999;Pizette and Niswander, 2000). BMPs and the closely related growth and differentiation factors (Gdfs) belong to the transforming growth factor-beta (Tgfb) superfamily and in mammals comprise 21 members.…”
Section: Condensation Of the Digit Anlagenmentioning
confidence: 99%
“…Bone morphogenetic protein (BMP) signaling is a major positive regulator of chondrogenesis (Duprez et al, 1996;Francis-West et al, 1996;Merino et al, 1999;Pizette and Niswander, 2000). BMPs and the closely related growth and differentiation factors (Gdfs) belong to the transforming growth factor-beta (Tgfb) superfamily and in mammals comprise 21 members.…”
Section: Condensation Of the Digit Anlagenmentioning
confidence: 99%
“…While a role for GDF-7/BMP-12 in chondrocyte biology and growth plate kinetics has, to our knowledge, not been reported in the literature, there is extensive evidence implicating the related molecule, GDF-5, in chondrocyte differentiation and maturation. [1][2][3][4][5][6][7] Most recently, 5-week-old female mice deficient in GDF-5 were shown to have the opposite phenotype in the proximal tibial growth plate relative to that seen in the present study with GDF-7 deficient mice of the same age and sex. 8 Compared to control growth plates, the physes from GDF-5 À/À animals had slower growth rates that were associated with a longer hypertrophic phase duration, whereas, in our current study, GDF-7 deficient growth plates had faster growth rates that were associated with a shorter hypertrophic phase duration.…”
Section: Discussionmentioning
confidence: 52%
“…[1][2][3][4][5][6][7] Five-week-old female mice deficient in one of these molecules, GDF-5, have additionally been shown to exhibit a significant reduction in proximal tibial growth rate due to a lengthened hypertrophic phase duration. 8 Most recently, Miyamoto and colleagues have demonstrated that Gdf5 appears to be a susceptibility gene for osteoarthritis, and that decreased Gdf5 expression may be associated with the development of this degenerative joint disease.…”
mentioning
confidence: 99%
“…This suggestive conclusion is partially supported by a recent cell fate study that used Gdf5-Cre mice mated with ROSA-LacZ mice (Koyama et al 2008). The growth differentiation factor Gdf5 is restrictively expressed in the interzone cells at the initial stage of the joint formation (Merino et al 1999;Storm and Kingsley 1999). Indeed, the Gdf5-Cre/ROSA-LacZ reporter-expressing cells were originally found in the joint interzone cells and subsequently predominant in articulating layers and accessory joint tissues (Koyama et al 2008).…”
Section: Resultsmentioning
confidence: 99%